2017
DOI: 10.29298/rmcf.v7i37.52
|View full text |Cite
|
Sign up to set email alerts
|

Intercepción de lluvia en bosques de montaña en la cuenca del río Texcoco, México

Abstract: El proceso de intercepción de lluvia por la masa arbórea, como componente del ciclo hidrológico en áreas forestales, está determinado, entre otras causas, por las condiciones climáticas, orográficas y por las características de la vegetación. Se presentan resultados de un programa de investigación que tiene como objetivo medir las cantidades de lluvia que interceptan tres comunidades forestales, en la cuenca hidrológico-forestal Río Texcoco. Se establecieron tres módulos de in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
2
3
Order By: Relevance
“…Flores-Ayala et al (2016) found a potential relationship for A. religiosa and a logarithmic relationship for P. hartwegii, with R 2 values much lower than those found in our study, since they obtained 0.58 and 0.42, respectively. In our study, the linear relationships (first-order polynomials) presented values of R 2 equal to 0.89 and 0.78 for A. religiosa and P. hartwegii, respectively, which are also higher than the values found by Flores-Ayala et al (2016).…”
Section: Canopy Rainfall Interceptioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Flores-Ayala et al (2016) found a potential relationship for A. religiosa and a logarithmic relationship for P. hartwegii, with R 2 values much lower than those found in our study, since they obtained 0.58 and 0.42, respectively. In our study, the linear relationships (first-order polynomials) presented values of R 2 equal to 0.89 and 0.78 for A. religiosa and P. hartwegii, respectively, which are also higher than the values found by Flores-Ayala et al (2016).…”
Section: Canopy Rainfall Interceptioncontrasting
confidence: 58%
“…The interception calculated for P. hartwegii and A. religiosa was 20.66 mm and 31.15 mm, respectively, corresponding to 16.37 and 24.68% of total rainfall. Flores-Ayala et al (2016) reported different total values in a study conducted on the same species as in this study, with 19.20% in P. hartwegii and 26.10% in A. religiosa. The difference in results between these two studies can be attributed to the fact that Flores-Ayala et al (2016) did not consider stemflow in their calculation of rainfall interception, since it was calculated by subtracting the throughfall from the incident precipitation.…”
Section: Canopy Rainfall Interceptioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Surface runoff (SR) refers to the rainfall that flows over the surface of the soil directly into nearby channels and bodies of water. Net precipitation (NP) is the amount of water that reaches the forest floor; it is a combination of throughfall and stemflow [17].…”
Section: Introductionmentioning
confidence: 99%
“…Forests also mitigate climate change through carbon sequestration, provide shelter for biodiversity, protect soil, and regulate the hydrological cycle (Keith et al, 2010; Mendoza‐Ponce et al, 2018). The rain interception process by the canopy of wooded vegetation, as a vital component of the hydrological cycle, is mainly determined by climate, orography, and vegetation structure (Flores Ayala et al, 2017; Link et al, 2004; Muzylo et al, 2009). In this sense, the amount of rain intercepted in a forest mass is expected to be determined mainly by the basal area to indicate the stand's density.…”
Section: Introductionmentioning
confidence: 99%